Pelatihan Pemasaran Digital Produk Perikanan di Desa Sungai Kupah, Kabupaten Kubu Raya - Wira Hadinata, Fitra; Andika Hutasoit, Kelvin; Hesti, Hesti; Theresia, Theresia; Zurba, Nabil (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
In the village of Sungai Kupah, there are groups of fish farmers divided into several activities, namely catfish farming, tilapia farming, and snakehead fish farming. Each activity group consists of 5 to 10 people. Fish farming is conducted in areas close to vegetable cultivation activities. The fish are traditionally maintained using fixed cages. There are 15 ponds managed, with a total pond area of approximately 1 hectare. The most productive fish are tilapia, with an annual production of 3 tons, followed by carp, catfish, and gourami, with variable production levels. The main issue faced by the fish farming groups in Sungai Kupah is the lack of skills and knowledge regarding marketing technology. The fish are only sold directly to the local community or to fish vendors at the nearest market. The results of fish farming are still considered suboptimal in terms of production quantity and sales profit. During harvest, not all fresh fish production can be absorbed by the market. The marketing target is currently only focused on meeting the needs of the local community and local markets. There has been an 80% increase in knowledge about website creation concepts. According to the participants, the website creation method was felt to be easier when tried directly, though it requires patience and persistence. Previously, no one in the community understood digital sales methods through websites; after the training, there was a 100% increase in skill change.